(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to identify the effect of a cognitive behavioral counseling program on developing the behavior of seeking counseling assistance among middle school students. From (10) sessions, two sessions per week, and the duration of each session is (45) minutes, and the researchers adopted the experimental approach, and the size of the research sample reached (42) students, and the statistical analysis program (spss for humanities) was used in analyzing the research data, and the researchers came out with a set of recommendations and proposals.Keywords: Counseling program, development, behavior of seeking counseling assistance, middle school students.